Upaya Meningkatkan Kemampuan Membaca Permulaan Melalui Media Pop Up pada Siswa Tunagrahita Ringan Kelas V di SDLB Bhakti Luhur Baumata Kupang - Mau, Theovilus Amandus; Wangge, Vinsensius; Selan, Ot Bil Wilson; Ajito, Timoteus (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve early reading skills through pop-up books for children with mild intellectual disabilities in grade V at SLB Bhakti Luhur Baumata Kupang. This research is a classroom action research. The subjects of the study were two grade V students with mild intellectual disabilities at SLB Bhakti Luhur Baumata Kupang. The research was conducted in two cycles. Data collection was carried out through early reading ability tests, observation of student participation, and documentation as supplementary data. Data analysis in this study used a comparative technique, which involves comparing pre-test scores with post-test scores and predetermined success criteria. The research results show that pop-up book media can improve initial reading skills in children with mild intellectual disabilities in grade V at SLB Bhakti Luhur Baumata Kupang. This is evidenced by the increase in scores for subject DM from 45 to 65, and for post-test II it reached 80. Subject EP's score increased from 50 to 70, and for post-test II it reached 85. The research findings indicate that pop-up book media can enhance the initial reading abilities of children with mild intellectual disabilities at SLB Bhakti Luhur Baumata Kupang. This can be proven by the average scores from student participation observation, which showed a very good category, reaching 90 in cycle I, while in cycle II the score reached 92. The scores consistently increased from the pre-test to post-test I and then to post-test II.